Medicinal Plants from Local Wisdom Sasak with Phytochemistry Course - Nora Listantia; Aliefman Hakim; A Wahab Jufri; Gunawan; AA Sukarso; Joni Rokhmat (International Journal of Contextual Science Education, 2024)
Phytochemistry course is a compulsory course in Bachelor of Pharmacy which should combine theory and practice. Phytochemistry courses are divided into Phytochemistry 1 and Phytochemistry 2 courses in the form of theory (2 credits) at several leading universities in Indonesia. The curriculum in the Pharmacy department or study program at universities in Indonesia does not all combine theory and practice in Phytochemistry Courses (University of Indonesia, Bandung Institute of Technology, Udayana University) although there are several universities using a 1 credit practicum in it such as UGM, UNAIR, and UNPAD. The purpose of this study is to model the practicum of Phytochemistry Course based on the local wisdom of the Sasak Tribe in West Nusa Tenggara Province by taking samples of medicinal plants from each regional district in NTB. This research is a literatured study with studies from various articles and practicum methods. By taking samples of mangosteen skin, betel leaves, castor bean, single garlic, soursop leaves, bay leaves, banten leaves, bebele leaves, tamarind leaves, and telang flowers. Practicum can develop higher-order thinking skills, this is because through practicum activities students are guided to carry out processes that can support thinking skills. The application of practicum will also link local wisdom, not only accept as a whole but can independently determine the sample of medicinal plants for extraction, so as to develop thinking skills in decision making in determining alternative compounds to be used.